Influence of structural and operating factors on mixing transfer of rotary energy recovery device through CFD simulation - Liu, Kai; Liu, Xuyu; Zhang, Xingkai; Shi, Baocheng; Wu, Lijuan; Zheng, Lixing (Frontiers in Energy Research, 2023)
The rotary energy recovery device (RERD) is an essential component in seawater desalination for decreasing the energy consumption of reverse osmosis plants. To research the complex flow fields and mixing motion in ducts of a rotary energy recovery device, a 3D numerical simulation was studied in this work. Three-dimensional vortex structures were visualized and identified based on the Q criterion. The effects of the operating condition and the structure parameter on the flow fields and the mixing motion had been discussed. Simulation results indicated that the interaction between vortices in the mixing zone and vortices in the duct entrance led to a high level of turbulence intensity and mixing degree. The mixing process could be controlled by the operating condition and the structure parameter. This paper provides a new approach to researching structural and operating factors on the mixing process of the rotary energy recovery device.